PENGARUH LATIHAN RELAKSASI GUIDED IMAGERY AND MUSIC (GIM) PADA KELAS IBU TERHADAP DERAJAT KECEMASAN IBU HAMIL MENGHADAPI PERSALINAN PERTAMA: STUDI DI PUSKESMAS MENINTING KABUPATEN LOMBOK BARAT - Ni Nengah Arini Murni; Suhartono Suhartono; Titi Suherni (poltekkes kemenkes mataram, 2014)
Abstract: Fear and anxiety in pregnant woman is actually a normal thing but if it cannot be overcame seriously, it will be affect and give great effect to mother and fetus physical and psychic. Objective to know the effect of GIM relaxation exercise in prenatal class toward the anxiety level of pregnant women in the first labor experience. Methods a quasi-experiment group, pre and post test with control group design. Sample of the study are pregnant women of primigravid in the three three-month periods which were taken by purposive sampling. The total samples are 34,17 in the intervention group and 17 in the control group. The measurement of anxiety variables is performed before and after the intervention process by using anxiety questionnaires of Hamilton Anxiety Rating Scale (HRSA). Data of the study is analyzed by using the Mann-Whitney test, Chi-quare, Independent Samples Test and Paired Samples Test. Results there were significant differences of anxiety scores, before and after treatment, in the intervention group (p = 0.001) and in the control group (p = 0.016). It is mean that GIM relaxation exercises in the prenatal class are effective in reducing maternal anxiety in their labor experience. The decrease of average anxiety scores in the intervention group was 8.2 (± 7.53) whereas in the control group was 2.3 (± 3.50), the average difference of anxiety scores between the two groups was significantly different (p-value = 0.003). It is mean that there are some effects of GIM relaxation exercise to the degree of maternal anxiety in the labor experience. Conclusion GIM relaxation exercise can be used as a model or an intervention alternative to reduce anxiety of pregnant women in dealing with labor experience